KEEFEKTIFAN GAME EDUKASI GIZI SEBAGAI MEDIA PROMOSI GIZI ANAK SEKOLAH DI MI NURUL ISLAM - Rinayati Rinayati; Mulyono Mulyono; Sri Wahyuning (VISIKES: Jurnal Kesehatan Masyarakat, 2016)
Indonesia experienced a double burden in dealing with nutritional problems, under nutrition and over nutrition. Based on Riskesdas 2013, Central Java was one of 16 provinces that above the national under weight prevalence. Malnutrition and obesity in Semarang is still high. According to BPOM 2014, there were four types of most polluted snack in schools; cube ice, cold drinks, jelly, and meatballs. The foods were contaminated with microbes hazardous materials, and excessive food additives. The health promotion for student is very important to influence and motivate them to learn and understand nutrition information and it can use educational games. This Study aims to determine the effectiveness of web-based nutritional education games as a health promotional media of nutritional information for MI Nurul Islam students. This research was a pre-experimental study, with one group pre-post test design.The study populations were 30 students of MI Nurul Islam Semarang. Tha data was analyzed by Wilcoxon test. The average level of nutrition knowledge before playing the education game was 42.9, then increased to 66.3 after playing it. Educational game significantly influenced the level of students’ nutrition knowledge (p = 0.0001). Keywords: nutrition, educational game